Efficacy of mefenoxam is affected by a lag period between application and inactivation of Pythium species - Abdullah AL-SADI (Phytopathologia Mediterranea, 2012)
A study was undertaken to investigate whether inactivation of Pythium by mefenoxam takes place as soon as it comes in contact with the fungicide. Laboratory experiments were conducted which involved three sensitive isolates of P. aphanidermatum (EC50<1 µg mL-1), three sensitive isolates of P. spinosum (EC50<1 µg mL-1) and two resistant isolates of P. aphanidermatum (EC50>100 µg mL-1). In liquid cultures, inactivation of the sensitive Pythium isolates by mefenoxam took place between 12 hr and >96hr at concentrations from 1 to 100 µg mL-1. The time required for inactivation was negatively correlated with the concentration of mefenoxam (P<0.05). Colonization of cucumber seeds placed at different distances from the sensitive Pythium inoculum in soil amended with 1 and 5 µg mL-1 mefenoxam occurred in the first 12 hr. However, colonization was reduced after 24 hr and was completely inhibited after 96 hr. Efficiency of colonization in the sensitive Pythium populations was found to have a negative correlation with the concentration of mefenoxam used. Growth and colonization by the resistant Pythium isolates were not found to be affected with mefenoxam. This study appears to be the first report of presence of a lag period between application of mefenoxam and time taken to inactivate Pythium.